Pre-eruptive Intra-Coronal Resorption: A report of two cases and review of the literature - Christopher Matesi; Rohan Jagtap; Mıchelle Briner Garrido; Joanne Briner Prenafeta; Andres Briner (European Annals of Dental Sciences, 2021)
Pre-eruptive intracoronary resorption is a rare condition mainly affecting pediatric patients. It is a radiographic finding in the dentin of the crown of an unerupted tooth just below the enamel-dentin junction. It is visualized in radiographs as a radiolucent coronal lesion of variable depth; it is well-defined and located in the dentin adjacent to the amelodentinal limit of an unerupted tooth. Historically, this lesion was misdiagnosed as caries and was misnamed pre-eruptive caries, when in reality they were pre-eruptive intracoronal resorptions. We present two rare cases of pre-eruptive intracoronary resorption in patients that needed radiographs for orthodontic purposes. The Oral amp; Maxillofacial Radiologist detected the existence of pre-eruptive intracoronary resorption in mandibular second premolars and mandibular second molar. These radiographic findings provided the clinician with the advantage of knowing this condition before teeth eruption, allowing for conservative treatment and periodic radiographic follow-up.